Sustainable investing: Encouraging Evidence for Investors. Issue 109 (17th September 2020) - Herrera, Gabriel; Brenneis, Michael
Abstract : Is sustainable investing a positive or negative contributor to outperformance? And how patient do investors need to be to capitalize on any positive effects? Our research results answer these questions, and our conclusions on the required time horizon may come as a surprise for investors hesitating to introduce sustainable investing, write Gabriel Herrera and Michael Brenneis.